SysPro:An Android Mobile Application for the Course System Programming - Dol, Sunita M.; Patnaik, P. S. R. (Journal of Engineering Education Transformations, 2025)
Mobile devices have become attractive learning devices in education sector. The majority of the existing research has focused primarily on the value of mobile learning for students and instructor. Mobile learning offers modern ways to support learning process through mobile devices. SysPro is an android mobile application for the course System Programming of Third Year Computer Science and Engineering. This application contains study material, power point presentations, quiz, question bank and games like crosswords; word search, word scramble and word match for every unit of this course. The APK file for this mobile application is available on the URL-https:// play.google.com/store/apps/details?id=in.witsolapur. sysproapp while the framework for SysPro is available on the Github URL: https://github.com/sunitamdol/SysPro or https://github.com/psrpatnaik/syspro.